2010
DOI: 10.1016/j.molstruc.2010.03.016
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational spectroscopic studies and computational study of quinoline-2-carbaldehyde benzoyl hydrazone

Abstract: a b s t r a c tFT-IR spectrum of quinoline-2-carbaldehyde benzoyl hydrazone (HQbÁH 2 O) was recorded and analyzed. The synthesis and crystal structure data are also described. The vibrational wavenumbers were examined theoretically using the Gaussian03 package of programs using HF/6-31G(d) and B3LYP/6-31G(d) levels of theory. The data obtained from vibrational wavenumber calculations are used to assign vibrational bands obtained in infrared spectroscopy of the studied molecule. The first hyperpolarizability, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(13 citation statements)
references
References 78 publications
1
12
0
Order By: Relevance
“…The C-N stretching is observed at 1248 cm -1 (IR), 1319, 1253 cm -1 (Raman), 1323, 1246 cm -1 (SDD) while C-N stretching is reported[37] at 1205 cm -1 . Another C=O stretching mode is theoretically observed at 1577 cm -1 which is in agreement with the reported values for similar quinoline derivatives[38]. For Quinoline ring, C-Cl stretching absorption is observed in the broad region between 850 and 550 cm -1[39,31].…”
supporting
confidence: 88%
See 1 more Smart Citation
“…The C-N stretching is observed at 1248 cm -1 (IR), 1319, 1253 cm -1 (Raman), 1323, 1246 cm -1 (SDD) while C-N stretching is reported[37] at 1205 cm -1 . Another C=O stretching mode is theoretically observed at 1577 cm -1 which is in agreement with the reported values for similar quinoline derivatives[38]. For Quinoline ring, C-Cl stretching absorption is observed in the broad region between 850 and 550 cm -1[39,31].…”
supporting
confidence: 88%
“…It is seen that the N 11 -C 13 -O 14 bond angle (121.8°) is considerably greater than the N 11 -C 13 -C 17 angle (116.0°), which is explained as due to a decrease in the repulsion between the lone pairs present in N 11 and O 14 atoms [44]. The dihedral angle H 19 -N 18 -C 20 -O 21 is reported as 172.0° [38], while we observe this at -157.0° which denoted a tilting from the plane.…”
Section: Optimized Geometrical Parametersmentioning
confidence: 99%
“…The ring breathing mode of the mono substituted phenyl ring is assigned at 1013, 1006 cm −1 (IR), 1000 cm −1 (Raman) and at 1009, 1003 cm −1 (DFT) for BZL [51, 52, 53]. In order to investigate the performance and vibrational wavenumbers of the title compounds, root mean square deviation (RMSD) between calculated and observed wavenumbers were calculated [54]. The RMSD of the observed IR bands are found to be 5.1 (BZL), 10.3 (DMB), 7.8 (DFB), 4.7 (DCB) and 7.3 (DBB).…”
Section: Resultsmentioning
confidence: 99%
“…49 Within this study, 49 the C¼O stretching vibration is observed at 1613.2 and 1749.9 cm À1 , whereas DFT calculation gives C¼O stretching mode at 1647.27 and 1738.00 cm À1 . For quinolone-2-carbaldehyde benzoyl hydrazine molecule by Sheeja et al, 50 C¼O stretching mode has been reported at 1655 cm À1 in the IR spectrum and calculated at 1624 cm À1 in the DFT model. By Demir et al, 42 this band has been identi¯ed as the coupling band and observed 1650/1676 cm À1 as (C¼O2þC¼O3) and calculated 1705 cm À1 (B3LYP) and 1717 cm À1 (B3PW91).…”
Section: Benzoyl Group Vibrations (With Ketone Carbonyl)mentioning
confidence: 96%